1999
DOI: 10.1016/s0960-9822(00)80081-0
|View full text |Cite
|
Sign up to set email alerts
|

The four-jointed gene is required in the Drosophila eye for ommatidial polarity specification

Abstract: The clonal phenotypes, time of requirement and regulation of four-jointed are consistent with it acting in ommatidial polarity determination as a second signal downstream of Notch, JAK/STAT and Wingless. Interestingly, it appears to act redundantly with unknown factors in this process, providing an explanation for the previous failure to identify a second signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
174
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(182 citation statements)
references
References 32 publications
5
174
0
3
Order By: Relevance
“…Four jointed (Fj) is a putative secreted type II trans-membrane molecule that is expressed in a broad gradient across the developing eye (Figure 3c; Brodsky and Steller, 1996;Villano and Katz, 1995). Both fj gain-and loss-of-function clones produce ommatidial inversion phenotypes as predicted for a di usible second signal proposed to be downstream of the Wingless and JAK/STAT pathways (Zeidler et al, 1999a). Interestingly, fj expression is regulated by both Upd and the JAK/STAT pathway as would be expected of a bona ®de second signal.…”
Section: A Second Signal and Ommatidial Polarity Determinationmentioning
confidence: 67%
See 2 more Smart Citations
“…Four jointed (Fj) is a putative secreted type II trans-membrane molecule that is expressed in a broad gradient across the developing eye (Figure 3c; Brodsky and Steller, 1996;Villano and Katz, 1995). Both fj gain-and loss-of-function clones produce ommatidial inversion phenotypes as predicted for a di usible second signal proposed to be downstream of the Wingless and JAK/STAT pathways (Zeidler et al, 1999a). Interestingly, fj expression is regulated by both Upd and the JAK/STAT pathway as would be expected of a bona ®de second signal.…”
Section: A Second Signal and Ommatidial Polarity Determinationmentioning
confidence: 67%
“…The identity of a putative second signal has remained elusive despite the fact that a number of predictions regarding the molecular nature and expression pattern of the second signal can be made (Zeidler et al, 1999b). However, a recent report has described the identi®cation of such a molecule (Zeidler et al, 1999a). Four jointed (Fj) is a putative secreted type II trans-membrane molecule that is expressed in a broad gradient across the developing eye (Figure 3c; Brodsky and Steller, 1996;Villano and Katz, 1995).…”
Section: A Second Signal and Ommatidial Polarity Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression is graded being highest in the distal wing/leg, and misexpression studies have demonstrated that fj is sufficient to direct ectopic joint formation (Brodsky and Stellar, 1996;Buckles et al, 2001;Strutt et al, 2004). In addition in Drosophila, fj controls planar polarity, determining the orientation of the bristles/hairs in the wing, leg, and anterior abdomen, and in the eye, the polarity of the ommatidia (Zeidler et al, 1999a(Zeidler et al, ,b, 2000Yang et al, 2002;Simon, 2004). Fj has also been implicated in vein patterning in the wing (Zeidler et al, 2000;Casal et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that fj is a type II transmembrane glycoprotein, and in support of this, it has been shown that it can be proteolytically cleaved, giving rise to a secreted protein lacking the N-terminus (Villano and Katz, 1995;Buckles et al, 2001). Truncated forms of fj have also been identified in the medium of fj-expressing Drosophila S2 cells, and misexpression studies in Drosophila have shown that fj can act non-cell-autonomously (Tokunaga and Gerhart, 1976;Zeidler et al, 1999aZeidler et al, ,b, 2000Buckles et al, 2001). However, other studies have shown that it does not have to be secreted to have full activity; indeed, Golgi-localized fj was found to have higher activity than secreted forms, suggesting that it modulates the function/processing of other proteins such as ds and ft (Strutt et al, 2004).…”
Section: Introductionmentioning
confidence: 99%